2016
DOI: 10.1155/2016/2951658
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Residence Floor Level and Cardiovascular Disease: The Health and Environment in Oslo Study

Abstract: Background. Increasingly more people live in tall buildings and on higher floor levels. Factors relating to floor level may protect against or cause cardiovascular disease (CVD). Only one previous study has investigated the association between floor level and CVD. Methods. We studied associations between floor of bedroom and self-reported history of stroke, venous thromboembolism (VTE), and intermittent claudication (IC) among 12.525 inhabitants in Oslo, Norway. We fitted multivariate logistic regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Apart from these disadvantages, high rise apartment residents have a lot of health benefits such as better respiratory health [10]. It is reported that higher the floor of residence, the lower the risk of cardiovascular diseases [11] [12]. Some of the perceived benefits of high rise buildings are unobstructed scenery, clean air, less noise, privacy and light [13].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these disadvantages, high rise apartment residents have a lot of health benefits such as better respiratory health [10]. It is reported that higher the floor of residence, the lower the risk of cardiovascular diseases [11] [12]. Some of the perceived benefits of high rise buildings are unobstructed scenery, clean air, less noise, privacy and light [13].…”
Section: Introductionmentioning
confidence: 99%